1988
DOI: 10.1111/j.1349-7006.1988.tb01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement by Leukocyte Adherence Inhibition of Autosensitization of Cancer Patients to Myelin Basic Protein

Abstract: In vitro cell‐mediated immunity was assayed by leukocyte adherence inhibition (LAI) to determine the extent of autosensitization to myelin basic protein (MBP). Leukocytes from 123 cancer patients, 16 patients freed of cancer, 135 patients with benign disease, and 26 patients with destruction of nervous parenchyma were tested. Most patients with cancer reacted to MBP: 92%, 93%, 82%, 78%, 75% and 62% for pancreatic, colonic, esophageal, lung, ovarian and breast. Few patients with benign diseases reacted to MBP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Studies have shown that MBP plays a role in immunity: it was serially measured in 177 CSF samples from 33 patients with leptomeningeal metastases and compared to 34 cancer controls to determine the degree of autosensitization to MBP [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MBP plays a role in immunity: it was serially measured in 177 CSF samples from 33 patients with leptomeningeal metastases and compared to 34 cancer controls to determine the degree of autosensitization to MBP [45].…”
Section: Discussionmentioning
confidence: 99%